Perspektif Pendidikan Agama Islam terhadap Pembinaan Santri di Dayah Darul Ulum Al Munawarah Lhokseumawe - Nuruzzahri Nuruzzahri (Multiverse: Open Multidisciplinary Journal, 2025)
This study examines the perspective of Islamic Religious Education on child development at Dayah Darul Ulum Al Munawarah, Lhokseumawe, focusing on educational practices, supporting factors, and existing constraints. The research addresses how caregivers conceptualize and implement child development strategies within an Islamic boarding school context. Employing a qualitative field research design, data were systematically collected through observation, in-depth interviews, and documentation. The findings reveal that caregivers apply a combination of authoritarian, democratic, and permissive parenting patterns to optimize child development. Educational methods include exemplary conduct, moral advice, individualized attention, habituation of virtuous behavior, and the application of proportional disciplinary measures. Child development is reinforced through structured Islamic activities such as congregational prayers, Qur’anic recitation, religious lectures, spiritual–physical activities, and periodic evaluations and competitions. Supporting factors consist of caregivers’ religious knowledge, alignment of institutional vision and mission, patience, sincerity, exemplary behavior, and clear institutional regulations. Conversely, inhibiting factors include weak commitment among some administrators, limited pedagogical experience and innovation, and recurrent student rule violations. Overall, the study argues that effective child development in Islamic educational institutions depends on coherent educational leadership, consistent institutional commitment, and adaptive pedagogical practices.